"Do you really need to ask me that now?": a self-audit of interruptions to the 'shop floor' practice of a UK consultant emergency physician. Issue 11 (22nd November 2011) - Allard, Jon; Wyatt, Jonathan; Bleakley, Alan; Graham, Blair
Abstract : Objectives: To map interruptions encountered by a senior physician performing a variety of everyday tasks on an emergency department (ED) 'shop floor' in the UK in order to identify tasks most likely to be interrupted, modes of interruption and those interruptions most likely to result in breaks as suspension of the original task. Methods: A self-observational audit study of interruptions was undertaken by a consultant emergency physician in a medium-sized ED over 25 separate shifts totalling 119 h. The main outcome measures were type and occurrence of interruption in relation to mode of original task. 'Success' of interruptions and number of outstanding tasks were also recorded. Results: 718 interruptions were recorded, with an average of 6 per hour. A mean number of 2.44 outstanding tasks were recorded on each occasion of interruption. Verbal advice, telephone calls and interpretations of x-rays were the most common forms of interruption. 498 interruptions (69%) were successful, defined as interruptions that resulted in a task break (over-riding and suspension of the original task). The most successful interruptions were calls to the resuscitation room (95%). Interruptions from electronic telecommunications systems were extensive (33% of total) with success dependent on the type of communication system. Telephone conversations were rarely interrupted (16% compared with a mean of 69%). Conclusions: Overt electronic communication systems may have a disproportionate impact in determining the likelihood for successful interruptions. Formal consideration of how to prioritise and manage interruptions from various channels could be usefully added to emergency medicine education and training.